2021
DOI: 10.7717/peerj.11113
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and cooking properties of commercial Thai rice noodles

Abstract: One of the most popular and abundant traditional foods in Asian countries is dried rice noodles. In fact, the demand for this product has increased steadily around the world in recent years. The qualities of rice noodles are directly related to the specific preferences of consumers. Hence, the present study aimed to determine the properties of eight commercial dried rice noodles that are readily available in most Thai markets. The specific properties under investigation and comparison in this study were proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Additionally, puddings, and soft cakes can benefit from these characteristics ( Falade and Christopher, 2015 ). Due to the creation of a stronger three-dimensional network, high amylose rice can give products firmness and crispness, which could be used in foods like snacks, noodles, and extruded goods that require a hard texture ( Kraithong and Rawdkuen, 2021 ; Wang et al, 2016 ). The estimated food energy is also calculated and presented differently among rice varieties, which is varied from 350.82 kcal/100 g (Upland brown rice) to 362.73 kcal/100 g (RD43 white rice).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, puddings, and soft cakes can benefit from these characteristics ( Falade and Christopher, 2015 ). Due to the creation of a stronger three-dimensional network, high amylose rice can give products firmness and crispness, which could be used in foods like snacks, noodles, and extruded goods that require a hard texture ( Kraithong and Rawdkuen, 2021 ; Wang et al, 2016 ). The estimated food energy is also calculated and presented differently among rice varieties, which is varied from 350.82 kcal/100 g (Upland brown rice) to 362.73 kcal/100 g (RD43 white rice).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of a substance to produce a viscous paste or gel after cooking and cooling, as well as the resistance of the paste to shear force during stirring, are both indicated by the final viscosity, which is one of the metrics most frequently used to characterize the quality of starch products ( Maziya-Dixon et al, 2007 ). High retrogradation of starch molecules might have contributed to high final viscosity of rice flour by promoting starch re-crystallization process ( Kraithong and Rawdkuen, 2021 ; Maziya-Dixon et al, 2007 ). The highest final viscosity also was found in flours of Luangpatue rice in white form (1366 BU) and brown form (1206.5 BU), which consistent with result of their amylose content and also indicated that these flours is suitable for producing rice noodles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These crosslinks generated higher setback viscosity compared to JMRF only. High setback or high amylose retrogradation imparted good rice noodle quality through reinforcement of the amylose network [24,25].…”
Section: Pasting Propertiesmentioning
confidence: 99%